2009
DOI: 10.1017/s1751731108003285
|View full text |Cite
|
Sign up to set email alerts
|

Effect or ractopamine on growth and body composition of pigs during compensatory growth

Abstract: The purpose of this study was to measure the growth and body composition of pigs during normal or compensatory growth from 60 to 100 kg, without (cont) or with ractopamine (rac) supplementation (20 mg/kg of diet). Thirty-four pigs were scanned by dual X-ray absorptiometry (DXA) for body composition analysis at a starting weight of 61.4 6 0.3 kg and at a final weight of 100.4 6 0.5 kg. Half the pigs were fed ad libitum throughout (8 cont and 9 rac). The other half were fed at maintenance for 8 weeks and then sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 33 publications
0
7
0
1
Order By: Relevance
“…Ractopamine hydrochloride increases the amount of lean meat and decreases the amount of carcass fat when fed to swine during the last 50 kg of gain, also increasing the rate of weight gain and feed conversion (Anderson et al, 1989;Merkel et al, 1987;Watkins et al, 1990;Williams et al, 1994). The biochemical basis of ractopamine effects is increasing the nitrogen retention, protein synthesis, enhancing lipolysis and suppressing lipogenesis (Apple et al, 2007;Armstrong et al, 2004;Carr et al, 2005;Mills, 2002;Mitchell et al, 1990;Mitchell, 2009). Illegal use of ß 2 -agonists in 5-to 10-fold therapeutic doses leads to accumulation of these compounds in animal tissues such as liver, kidney and muscle (Smith, 1998;Smith & Shelver, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Ractopamine hydrochloride increases the amount of lean meat and decreases the amount of carcass fat when fed to swine during the last 50 kg of gain, also increasing the rate of weight gain and feed conversion (Anderson et al, 1989;Merkel et al, 1987;Watkins et al, 1990;Williams et al, 1994). The biochemical basis of ractopamine effects is increasing the nitrogen retention, protein synthesis, enhancing lipolysis and suppressing lipogenesis (Apple et al, 2007;Armstrong et al, 2004;Carr et al, 2005;Mills, 2002;Mitchell et al, 1990;Mitchell, 2009). Illegal use of ß 2 -agonists in 5-to 10-fold therapeutic doses leads to accumulation of these compounds in animal tissues such as liver, kidney and muscle (Smith, 1998;Smith & Shelver, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…(1,2) As ractopamine increases nitrogen retention, protein synthesis and lipolysis while suppressing lipogenesis, it could be used to improve protein-to-fat ratio and produce leaner carcasses. (3)(4)(5) As a feed additive for swine and cattle, ractopamine has been approved in some countries including USA, (1) but its use is prohibited in the European Union. (6) Although all earlier incidents of poisoning were caused by clenbuterol as a representative of the group of β-agonists, the European Union banned the use of these substances and requires strict monitoring for their illegal use.…”
Section: Introductionmentioning
confidence: 99%
“…Compensatory growth enables either complete or partial compensation depending on the persistence of the increased growth rate, although there may be no increase in growth rate and hence no compensation. Age at restriction, the severity and duration of the restriction are three major factors contributing to the variation in compensatory growth response of animals (Ryan, 1990;Mitchell, 2009). Several studies have reported some mechanisms that would be associated with compensatory growth, such as feed intake (Graham and Searle, 1979;Hornick et al, 1998;Mc Gregor et al, 2012), growth efficiency (Ryan, 1990;Connor et al, 2010;Keogh et al, 2015a), maintenance energy requirements (Fox et al, 1972;Butler-Hogg and Tulloh, 1982;Sainz et al, 1995) and tissue deposition patterns (Levy et al, 1971;Keogh et al, 2015b).…”
Section: Introductionmentioning
confidence: 99%